Characteristics of Sleep Structure Assessed by Objective Measurements in Patients With Amnestic Mild Cognitive Impairment: A Meta-Analysis - Cai, Sijie; Li, Tingting; Zhang, Li; Shi, Longhua; Liao, Jingling; Li, Wenfang; Cheng, Guangwen; Tan, Wei; Rong, Shuang (Frontiers in Neurology, 2020)
Objectives: This study aims to explore the differences of sleep structure between patients with amnestic mild cognitive impairment (aMCI) and elderly with normal cognition, which help to provide evidence for the relationship between sleep disturbances and cognitive impairment. Methods: Systematic review and meta-analysis were conducted on the literature on sleep parameters obtained by polysomnography or actigraphy in patients with aMCI. PubMed and EMBASE databases were searched up to April 2020. Inclusion and exclusion criteria were established according to evidence-based medicine methods, and data of all eligible study were meta-analyzed using Review Manager 5.3 software. Results: Among the 1171 literature articles on sleep structure of patients with MCI, eight case-control studies met the inclusion criteria and were included in this meta-analysis. A total of 278 subjects were included, of which 103 were patients with aMCI and 175 were elderly with normal cognition. The results showed that sleep efficiency (SE) and slow wave sleep (SWS) of patients with aMCI were significantly lower than those of healthy elderly. Compared with the control group, percent of stage 1 of non-rapid eye movement (N1%) in the aMCI patients group increased, and percent of stage 2 of non-rapid eye movement (N2%) decreased. Conclusions: Patients with aMCI may experience more severe sleep disturbances than normal cognitive elderly. There were specific changes especially SE and SWS in the sleep structure of patients with aMCI when compared to those with normal cognition.